Contested Killings Replication: A Comment on Morris and Shoub (2023) - Jacques Courbe; Joshua Ferrer; Graham Straus (Institute for Replication (I4R), 2024)
Morris and Shoub (2024) study whether fatal police shootings mobilize voter participation in presidential elections. They use a discontinuity-in-time design to causally estimate the effect of a police killing on turnout, comparing the voter participation of communities near a killing before and after election day. Morris and Shoub (2024) find that police killings spurred increased turnout, especially in Black communities, where the killing trended on Google, where the community was plurality Black, and where the victim's race was Black. They find that the local average treatment effect on participation within a quarter-mile radius of a police killing is upwards of 7 percentage points and statistically significant at the 95% level of confidence. We encounter difficulties when attempting to reproduce the analysis, but are able to replicate the main results using similar data. In fact, we find the effect of a proximate police killing on participation to be upwards of 8 percentage points.
Keywords: P00; 330; Voter turnout; criminal justice; race and ethnicity politics; police violence; discontinuity-in-time